Massive Lipomatous Hypertrophy of the Right Atria - López-Candales, Angel (Medknow Publications & Media Pvt Ltd, 2013)
A case of a 70-year-old female with a history of hypertension, atrial fibrillation, pacer implantation for symptomatic bradycardia, and a prior cerebrovascular accident, and had developed persistent methicillin-sensitive Staphylococcus aureus bacteremia is reported here. As part of her evaluation, a transesophageal echocardiogram was performed, and even though no vegetations were seen on either pacer wires or cardiac valves, a massive homogeneous thickening of the superior portion of the interatrial septum extending to the posterior and roof portions of the right atrial wall as well as to the superior vena cava causing proximal compression of this vessel was noted. Computed tomographic examination of the chest helped to determine that this mass density was not a tumor but in fact intrapericardial fat. Imaging findings and existing literature on this topic are reviewed.